2021
DOI: 10.1149/1945-7111/ac201e
|View full text |Cite
|
Sign up to set email alerts
|

Review—Technologies and Materials for Water Salinity Gradient Energy Harvesting

Abstract: Obtaining energy from renewable resources is a powerful measure in eliminating the impact of greenhouse gas and environmental pollution. At present, only 20% of energy comes from renewable energy sources, such as wind, solar, ocean, biomass, and geothermal energy. Sea water is the most abundant natural resource, accounting for more than 97% of total water resources. From a practical standpoint, it is very desirable to use seawater for conversion and energy production. Salinity gradient energy is the chemical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The cycle curve is drawn by using the changes of capacitor voltage and electric quantity in the four step cycle process as a measure of whether the system generates net energy. ,, The cycle curve is similar to the Carnot cycle diagram of a heat engine, as Figure d shows. The area enclosed by the voltage changes with the electric quantity is approximate to a parallelogram, E = ∮ V ·d Q , and if the discharge voltage is higher than the charging voltage without changing the electricity quantity, it will be a counterclockwise cycle, so the cycle is a productivity process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cycle curve is drawn by using the changes of capacitor voltage and electric quantity in the four step cycle process as a measure of whether the system generates net energy. ,, The cycle curve is similar to the Carnot cycle diagram of a heat engine, as Figure d shows. The area enclosed by the voltage changes with the electric quantity is approximate to a parallelogram, E = ∮ V ·d Q , and if the discharge voltage is higher than the charging voltage without changing the electricity quantity, it will be a counterclockwise cycle, so the cycle is a productivity process.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we did not use inert porous electrodes, but instead used pseudocapacitive electrodes with a high specific capacity and a low self-discharge. This technology does not require any expensive ion exchange membranes and can also achieve good salinity gradient energy extraction results. , A hydrothermal method is used to prepare pure layered manganese phosphate hydrate powder with sodium ion intercalation, which is called Na-Mn 3 (PO 4 ) 2 ·3H 2 O. Through material testing and characterization it is found that the electrochemical performance of the Na-Mn 3 (PO 4 ) 2 ·3H 2 O that the Na + preintercalated layer has been greatly improved compared with that of Mn 3 (PO 4 ) 2 ·3H 2 O.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, none of these applications involve voltage levels comparable to those present in CapMix cells. As already indicated at the end of Section 1, the literature is mainly focused on the charging process related to mobility applications [32,33] when the storage system is based on both supercapacitor and battery systems, but nothing has been found related to CapMix cells, which typically are loaded with a resistor [34], as primary sources with polarity inversion and very low voltage for energy transfer to the grid.…”
Section: Electronic Converter Topologymentioning
confidence: 99%
“…16 The anions and anions in the high concentration solution enter the low concentration solution under the action of osmotic pressure to form an ion flow. [17][18][19] The electrodes on both sides form a circuit by external resistance, and finally form a current, [20][21][22] but it has the same difficulties as the PRO of high cost and easy pollution. 23 The CapMix extracts salinity gradient energy through electrode potential difference, 6,7,24 which includes capacitive double-layer expansion (CDE), capacitive Donnan potential (CDP) and mixing entropy battery (MEB).…”
mentioning
confidence: 99%